2020
DOI: 10.7150/thno.46771
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Manganese doped silica nano GSH-cleaner for treatment of Liver Cancer by destroying the intracellular redox homeostasis

Abstract: Background: Glutathione (GSH), the primary antioxidant in cells, could fight against oxidative stress. Tumor cells display a higher GSH level than normal cells for coping with the hyperoxidative state, which meets the requirements of enhanced metabolism and vicious proliferation. Therefore, the consumption of GSH will lead to cell redox imbalance and impede life activities. Herein, targeted sorafenib (SFB) loaded manganese doped silica nanoparticle (FaPEG-MnMSN@SFB) was constructed, which could dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 48 publications
2
68
0
Order By: Relevance
“…GSH is one of the most important antioxidants and protects cells against lipid peroxide damage [ 38 , 61 ]. By utilizing GSH, ferroptosis is antagonized because lipid peroxides are reduced to their corresponding alcohols [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GSH is one of the most important antioxidants and protects cells against lipid peroxide damage [ 38 , 61 ]. By utilizing GSH, ferroptosis is antagonized because lipid peroxides are reduced to their corresponding alcohols [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…By utilizing GSH, ferroptosis is antagonized because lipid peroxides are reduced to their corresponding alcohols [ 9 , 11 ]. It is also not difficult to understand that, exhausting GSH is a potential way to trigger ferroptosis [ 38 , 62 , 63 ]. GSH can be synthesized from three critical amino acids: cysteine, glutamate and glycine [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS measurements further supported this conclusion. Studies have shown that oxidative stress is closely associated with apoptosis, and if the ability of cells to resist oxidative stress is diminished, intracellular ROS increase and lead to cell apoptosis [ 25 28 ]. Western blotting was used to detect the expression of apoptosis-associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the advantages of various new materials in cancer prevention and treatment have gradually emerged. Previous studies demonstrated that manganese-doped silica nanoparticle (MnMSN) can deplete GSH, and on-demand drug release can be achieved by loading sorafenib into MnMSN, while dual induction of ferroptosis is achieved by depletion of GSH and inhibition of intracellular GSH synthesis, showing efficient anti-HCC activity ( 17 ). Jiang and colleagues observed that a platelet membrane-camouflaged magnetic nanoparticle could sensitize ferroptosis by inhibiting system Xc − , which lead to immunosuppressive M2 TAM reversely polarize to the anti-tumor M1 phenotype, further increasing response to immunotherapy ( 18 ).…”
Section: Introductionmentioning
confidence: 99%